Practice theories and supply chain~sustainability: A~systematic~literature review and~a research agenda - Minelle E. Silva; Morgane M. C. Fritz; Wael Hassan El-Garaihy (Modern Supply Chain Research and Applications, 2022)
Purpose - This paper presents an investigation into the ways the term "practice" is commonly referenced in supply chain management academic papers. Scholars have not yet developed a common understanding of the meaning and do not use practice theories when examining practices related to sustainability management in supply chains. Hence, the authors highlight theoretical gaps and make recommendations for future research. Design/methodology/approach - Grounded in a systematic literature review of 232 peer-reviewed papers published in operations and supply chain management journals, a qualitative content analysis was conducted using both a deductive and an inductive approach. Findings - Results show that supply chain sustainability (SCS) scholars seem barely interested in increasing the understanding of the term "practice," widely used in the literature to refer to a practical context. Moreover, a clear distinction between being practical and using practice theories to study SCS practices is needed. A descriptive and critical analysis revealed eight key supply chain practices connected to sustainability, with a clear reflection on their meaning. As awareness of practice theories for research on SCS is limited, few recommendations for researchers and practitioners were identified. Originality/value - Unlike prior literature reviews, the authors reinforce the need to increase the maturity of the SCS field by going beyond superficial theoretical building. Practice theories pathways are provided to enlighten scholars on how to avoid using the term "practice" as taken-for-granted and on how to deal with SCS research and practice.
Keywords: 650; Practice theories; Practice-based studies; Practice-based view; Supply chain practices; Supply chain sustainability; Systematic literature review